Concept Development Of Halal Assurance System In The Chicken Slaughter House (Case Study Of Chicken Meat Industry) - Wiwit Estuti; Rizal Syarief; Joko Hermanianto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
The application of effective halal assurance system model was one of producer’s effort to supply halal food for Moslem consumers. The objective Of this research was to develop halal assurance system concept which is consist of halal manual. Halal Standard Operating Procedure, Guideline, and Work Instruction which should be applied at Chicken Slaughter House. flied research used descriptive method by distributing questionnaire, direct observation, on-site verification and halal assurance system assessment on two Chicken Slaughter House. The halal assurance system assessment was conducted based on ISO 9000, 2000 guideline of arrangement of HACCP system. The conclusion of this research was that this Halal Assurance System was suitable to be used as a standard for Chicken Slaughter House. The document change on both industry was that of applied halal assurance system. It was found that there were two kinds of haram Critical Control Point, which were two points at raw material and four point at chicken production process. Keywords : concept, model, assurance, halal, slaughter house